Three new species and new records of Clastobasis Skuse (Diptera: Mycetophilidae) from Japan and the Kuril Islands - Kurina, Olavi (Zootaxa, 2020)
Three new Clastobasis Skuse species are described: C. ainuorum sp. n. (Kuril Islands, Iturup), C. kanabo sp. n. (Japan, Honshū) and C. menguali sp. n. (Japan, Honshū). The new species are figured, photographed and their systematics discussed. New records are provided for C. loici Chandler and C. subalternans Zaitzev, both from Japan (Honshū). The number of Palaearctic Clastobasis species is set up at eight including six of them restricted only to the Eastern Palaearctic. Clastobasis loici, previously known only from Europe, is described to have a Trans-Palaearctic distribution. A key to the Palearctic species of Clastobasis is provided and the distribution shortly discussed.